The Effect of Describing Picture Media on Students’ Speaking Skill at The Ninth Grade Student of MTs Mathla’ul Anwar Nambo Picung Pandeglang Banten in Academic Year 2021/2022 - Supriyanti, Iyet; Gumelar, Rizdki Elang; Munawaroh, Tatu (Journal of English Education Studies, 2024)
This research aims to determine the effect of describing picture on students’ speaking skill at the ninth grade student of MTs MA Nambo Picung Pandeglang. This study uses a quantitative approach with a quasi-experimental design. This research uses three concepts, namely pre-test, treatment and post-test. The pre-test would be carried out before giving treatment, the treatment would be carried out in five meetings, and post-test would be given after treatment. The results of data analysis showed that the mean of post-test both experimental and control class are different, they are 79.00 and 63.75. The result of t-test obtained is 0.000 ≤ α = 0.05. The result indicated the alternative hypothesis was accepted and the null hypothesis was rejected. This finding shows that the describing picture has significant effect on students' speaking skills. Based on the findings, coud be said that the media picture is very useful for teachers to improve students' speaking skills, and easy to learn for students.